Inhibition of Angiogenesis and Extracellular Matrix Remodeling: Synergistic Effect of Renin-Angiotensin System Inhibitors and Bevacizumab - Ren, Tianshu; Jia, Hui; Wu, Qiong; Zhang, Yan; Ma, Qun; Yao, Dong; Gao, Xudong; Xie, Danni; Xu, Zihua; Zhao, Qingchun; Zhang, Yingshi (Frontiers in Oncology, 2022)
Bevacizumab (Bev) is a humanized vascular endothelial growth factor monoclonal antibody that is used with chemotherapeutic drugs for the treatment of metastatic colorectal cancer (mCRC). Bev-induced hypertension (HT) is the most common adverse reaction during clinical practice. However, at present, appropriate antihypertensive agents for Bev-induced HT are unavailable. In this study, retrospective analysis of clinical data from mCRC patients who received renin-angiotensin system inhibitors (RASIs) showed significant survival benefits of overall survival (OS) and progression-free survival (PFS) over patients who received calcium channel blockers (CCBs) and patients who received no antihypertensive drug (NO: Y2020046 retrospectively registered). An experiment of HCT116 colon cancer cell xenografts in mice confirmed that combined treatment of Bev and lisinopril (Lis), a RASI, synergistically inhibited subcutaneous tumor growth and enhanced the concentration of 5-fluorouracil (5-Fu) in tumor tissues. Our results showed that the addition of Lis did not interfere with the vascular normalization effect promoted by Bev, but also inhibited collagen and hyaluronic acid (HA) deposition and significantly downregulated the expression of TGF-β1 and downstream SMAD signaling components which were enhanced by Bev, ultimately remodeling primary extracellular matrix components. In conclusion, RASIs and Bev have synergistic effect in the treatment of colorectal cancer and RASIs might be an optimal choice for the treatment of Bev-induced HT.